Multiplier Effects in Local and Regional Development - Domański, Bolesław; Gwosdz, Krzysztof (Quaestiones Geographicae, 2010)
The aim of the paper is to outline demand-driven multiplier mechanisms, the theory behind them, and applicable quantification methods (aggregate models and incremental methods). The authors discuss a number of key problems related to multiplier effects as fundamental mechanisms of local and regional development. The study of the magnitude, industry structure, spatial distribution, and key determinants of those effects can help understand growth mechanisms in local and regional economies and evaluate the advantages and disadvantages associated with new, e.g. foreign, investment. Furthermore, the results of earlier empirical studies of the magnitude, spatial distribution and determinants of multiplier effects are presented together with the outcomes of the authors' own study.